Measurements and modeling of temperature compensated surface acoustic wave resonators - Mohamad Ashari, Zainab; Sidek, Fatini; Nordin, Anis Nurashikin (2010)
Surface Acoustic Wave (SAW) resonators are key components in oscillators, frequency synthesizers and transceivers. One of the drawbacks of SAW resonators are that its piezoelectric substrates are highly sensitive to ambient temperature resulting in performance degradation. This work proposes a simple feedback control circuit which stabilizes the temperature of the SAW resonator, making it independent of temperature change. The circuit is based on the oven-control method which elevates the temperature of a resonator to a high temperature, making it tolerant to minor changes in the ambient temperature. This circuit consists of a temperature sensor, heaters and a comparator which turns the heater on and off depending on the ambient temperature. Several SAW resonators were tested using the designed circuit. Experimental results indicate that the temperature coefficient of frequency (TCF) decreased significantly from 130.44/ #x00B0;C to -1.11/ #x00B0;C when the circuit was utilized. An equivalent RLC circuit model of both the uncompensated and compensated SAW resonators are also presented.